2021
DOI: 10.3390/fluids6010043
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement inside Rectangular Channel by Means of Vortex Generated by Perforated Concave Rectangular Winglets

Abstract: Passive methods using vortex generators (VGs) to enhance heat transfer have been a concern of researchers in recent decades. This study is intended to investigate the strength of the vortex generated by VGs by trying to reduce the pressure drop in the flow. The present work also takes into account the influence of the vortex intensity on the improvement of heat transfer, which can be indicated by the low value of the synergy angle. Experiments were carried out in the current investigation to validate the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Validation was necessary to ensure that the experiments carried out were going in the right direction. This validation was carried out by comparing the current experiment with the experiment from Whitaker, for which validation results can be seen in previous studies [31]. In the validation, the current experimental conditions were adjusted to the experimental conditions used by Whitaker.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation was necessary to ensure that the experiments carried out were going in the right direction. This validation was carried out by comparing the current experiment with the experiment from Whitaker, for which validation results can be seen in previous studies [31]. In the validation, the current experimental conditions were adjusted to the experimental conditions used by Whitaker.…”
Section: Validationmentioning
confidence: 99%
“…Although the results of their study were not as expected, they showed a significant decrease in pressure drop. In a subsequent study, Syaiful et al (2021) tried to investigate the use of concave rectangular winglet (CRW) VGs for increasing the heat transfer rate, where CRW VGs showed a better thermal improvement than concave delta winglet (CDW) VGs [31]. As with previous studies, they found that pressure drops could be reduced with the use of perforated VGs compared with non-perforated VGs.…”
Section: Introductionmentioning
confidence: 96%
“…The computational domain consists of an upstream extended region, the test region, and an extended downstream region. Before entering the test section, the extended upstream region is used to obtain fully developed flow [21,22]. Subsequently, the air passes through the test section, which contains 56 pairs of the DW VGs arranged on the top and bottom surfaces of the flat plate in an inline configuration.…”
Section: Computational Domainmentioning
confidence: 99%
“…The surface of the circular channel is subjected to heat induction along the test section. The air passes through the extended downstream region, which helps prevent reverse flow [21,22]. The schematic of this computational domain is shown in Figure 4.…”
Section: Computational Domainmentioning
confidence: 99%
“…The results showed the heat transfer performance/volume (Qv) and pumping power/volume (Pv) increased by 12.5% and 7.41%, respectively, when using DWP on corrugated FTHE. Furthermore, Siwi et al [15] and Hendraswari et al [16] conducted a numerical analysis of DWP, CDWP, RWP, and CRWP with an angle of 15°. The study showed the concave VG outperformed the flat VG shape due to the generation of more significant vortices.…”
Section: Introductionmentioning
confidence: 99%